2012
DOI: 10.1590/s0102-311x2012001400018
|View full text |Cite
|
Sign up to set email alerts
|

Produtivismo e avaliação acadêmica na Saúde Coletiva brasileira: desafios para a pesquisa em Ciências Humanas e Sociais

Abstract: Este artigo problematiza alguns desafios que se impõem à produção do conhecimento nas Ciências Humanas e Sociais, no campo da Saúde Coletiva, sob o atual modelo que norteia as avaliações acadêmicas no Brasil. Para tanto, o artigo focaliza o enfoque qualitativo de pesquisa em Ciências Humanas e Sociais, analisando o seu estatuto ante outras tradições que com ele disputam hegemonia no campo da Saúde Coletiva, conjugando o diálogo com a literatura, notadamente proposições relativas aos campos sociais presentes na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
9

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 12 publications
0
5
0
9
Order By: Relevance
“…The co-participation of postgraduate students is gaining increasing importance in the evaluation of intellectual production. Historically, biomedical postgraduate programs have given more importance to papers published in journals that disseminate internationally relevant topics, are indexed in international databases, and quantify citation impact, whereas, in the field of humanities, postgraduate programs have focused their production on books [15][16][17].…”
Section: Intellectual Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…The co-participation of postgraduate students is gaining increasing importance in the evaluation of intellectual production. Historically, biomedical postgraduate programs have given more importance to papers published in journals that disseminate internationally relevant topics, are indexed in international databases, and quantify citation impact, whereas, in the field of humanities, postgraduate programs have focused their production on books [15][16][17].…”
Section: Intellectual Productionmentioning
confidence: 99%
“…There was a marked increase in the number of articles published in higher quality journals in the triennium 2010-2012, which is probably a result of CAPES policies aimed at stimulating international publication of research results and the emphasis given to projects with a biomedical approach [21]. Note that data from the 2013-2016 report [11] are not included in Table 3 because only relative values and indicators were given in the document, as opposed to previous reports [10,15], which provided both relative and absolute values of intellectual production parameters. The journal quality ranks of the Qualis system led to important considerations for improving evaluation criteria of multidisciplinary research fields, such as Food and Nutrition, as shown by the requests of different scientific fields.…”
Section: Qualis Journals: the Capes Journal Quality Rankingmentioning
confidence: 99%
“…These aspects lead to increased competitiveness among peers, the professional isolation of faculty members in their research group and, often, alienation at work (25)(26) . This concern has also been implicated in a global context, according to the report from the 2013 European Union Study Group on the Modernization of Higher Education, which recommends that the preponderance of research in relation to teaching in the definition of academic merit needs to be revised (27) .…”
Section: From Overvaluation To the Shortage Of Research: Effects On Fmentioning
confidence: 99%
“…Sem dúvida, como exposto por Maria Lúcia Magalhães Bosi 9 , a questão da avaliação acadê-mica da produção científica em ciências sociais na saúde coletiva é desafiante, especialmente quando referida às pesquisas qualitativas. Analisa que no padrão vigente predomina o que denomina "produtivismo", ou seja, a quantidade de artigos requeridos aos pesquisadores dentro de modelos de avaliação dessa produção científica que marginaliza formas de pesquisa (pesquisas com metodologias quantitativas), estilos de narrativas (as discursivas) e formas de divulgação (livros).…”
Section: Fórum Forumunclassified